OIP5 Is a Novel Prognostic Biomarker in Clear Cell Renal Cell Cancer Correlating With Immune Infiltrates - Gong, Mancheng; Li, Yongxiang; Song, Erlin; Li, Miaoyuan; Qiu, Shaopeng; Dong, Wenjing; Yuan, Runqiang (Frontiers in Immunology, 2022)
Opa interacting protein 5 (OIP5), overexpressed in some types of human cancers, has been reported to be associated with the carcinogenesis of human cancer. However, its contribution to cancer immunity remains unknown. However, the relationship between OIP5 and cancer immunity remains uncertain. In our research, we explored the different expression of OIP5 between 539 CCRCC and 72 normal renal tissues base on TCGA data set. We analyzed the associations of OIP5 expression and CCRCC progression and survival. Next, we compared immune cell profiles in cancerous tissues and normal tissues in the Cancer Genome Atlas (TCGA) CCRCC cohort. We found that the level of immune cell infiltration was correlated with the copy number of OIP5 gene in CCRCC. The effect of OIP5 on immune activity was verified by Gene Set Enrichment Analysis of RNA-seq data from 32 CCRCC cell lines in the public database. A pathway enrichment analysis of 49 OIP5-associated immunomodulators demonstrated the involvement of the T cell receptor signaling pathway, the JAK-STAT signaling pathway, the NF-kappa B signaling pathway and the primary immunodeficiency pathway. Using OIP5-associated immunomodulators, we constructed multiple-gene risk prediction signatures using the Cox regression model. Our results provided insights into the role of OIP5 in tumor immunity and revealed that OIP5 may be a potential immunotherapeutic target for CCRCC. Designated immune signature is a promising prognostic biomarker in CCRCC.